The discovery of Ottoman Greece knowledge, encounter, and belief in the Mediterranean world of Martin Crusius - Calis, Richard 1988- (Harvard University Press, 2025)
"The discovery of Ottoman Greece unearths forgotten research by the early modern philhellenist and Lutheran reformer Martin Crusius. His extensive study of Greek Orthodox life, including interviews with traveling alms-seekers, sheds light on European views of Greek decline under Ottoman rule as well as on the global ambitions of Lutheran reform"
Includes bibliographical references and index
Keywords: Crusius, Martin -- 1526-1607; Griechenland -- Motiv; Forschung